Value Added Tax (VAT) Technology Compliance Efficiency Oman - Khalil, Muhammad Khuram; Banawas Ajzoon, Taif Khalid; Naidu, Vikas Rao (Journal of Student Research, 2023)
This research paper aims to explore the influence of technology in streamlining VAT operations in Oman. It will use a mixed-methods approach, including a review of literature and a survey given to firms in Oman. The survey will look at the amount of technology implementation in Oman's VAT processes and the perceived advantages and difficulties of technology adoption. The study's findings will shed light on the existing level of technology usage in Oman's VAT procedures as well as any prospective advantages and drawbacks of doing so. The study will emphasize the value of technology in lowering compliance costs, minimizing mistakes, enhancing accuracy, and boosting efficiency in the VAT process.